A Case Study: Consumer Behavior of Frozen Fruit in terms of Preferences and Purchasing Power - Grace Putlia (Lembaga Pengembangan Manajemen dan Publikasi Imperium, 2022)
Frozen food or what is known as frozen food is the result of food preservation methods that are carried out by lowering the temperature to the freezing point, this aims to slow down the spoilage process. One published study found that frozen fruit was, in some cases, more nutritious. Of course, this is suitable when conditioned during a pandemic like today, because frozen fruit is more durable, of course, it can minimize the frequency of people going out to buy stock. But on the other hand, apart from the price of frozen fruit which tends to be more expensive, there is a paradigm in the community that fresh fruit is healthier than frozen fruit. Although it is undeniable that fresh ingredients have a high amount of nutrients at harvest, the nutrients will quickly break down when the food is picked, packaged, and displayed. These nutrients will break down even more when placed in the refrigerator. This research is a qualitative research with a case study design. A total of 23 informants as end consumers really helped the completion of this research. The results of this study found that the paradigm in society that fresh fruit is healthier than frozen fruit is still rolling down and down, on the other hand factors such as price are also another cause. Keywords: Case Study, Consumer Behavior, Consumption, Frozen Fruit, Preference.